Effects of oral sarcopenia and malnutrition on the elderly - Chieh Chen; Da-Ming Liao (Tungs’ Medical Journal)
Abstract Old-aged adults often suffer from nutrient deficiency or appetite loss resulting from taste and smell degeneration, poor oral and dental functions, and chewing and swallowing difficulties in addition to having poor digestion and gastrointestinal tract absorption or delayed stomach emptying. Consequently, anorexia and less food consumption occur, not to mention the medication–food interaction that will aggravate insufficient nutrient intake. Moreover, aged people tend to isolate or suffer from depression, and insomnia, which can all weaken and empty their body and soul, leading to undernourishment. Older adults who are picky eaters are 2.5 times more prone to develop weakness in the future than average individuals, as well as a significant increase in disability risk by 40%. Anorexia nervosa, which refers to a decline in appetite or food intake, is common in this population because of the degradation of chewing and swallowing functions. In fact, those who are 65 years old and above have a 21.8% chance of choking on food at least thrice a week, for which 12.8% of them were diagnosed with dysphagia, statistically equivalent to 1 out of every 10 old-aged adults having a mild or more severe swallowing disorder.